Body composition health is more than skin deep - Clark, Kristine L., 1953-; Healthy Learning Videos (Monterey, CA : Healthy Learning Videos, 2004)
This video reviews what body composition is, how it relates to weight, who should have a body composition test, and when that person should be tested
Instructor, Kristine Clark
Keywords: Body composition; Body composition -- Measurement; Body Mass Index